Selection of parental lines for plant breeding via genomic prediction - Chung, Ping-Yuan; Liao, Chen-Tuo (Frontiers in Plant Science, 2022)
A set of superior parental lines is imperative for the development of high-performing inbred lines in any biparental crossing program for crops. The main objectives of this study are to (a) develop a genomic prediction approach to identify superior parental lines for multi-trait selection, and (b) generate a software package for users to execute the proposed approach before conducting field experiments. According to different breeding goals of the target traits, a novel selection index integrating information from genomic estimated breeding values (GEBVs) of candidate accessions was proposed to evaluate the composite performance of simulated progeny populations. Two rice (Oryza sativa L.) genome datasets were analyzed to illustrate potential applications of the proposed approach. One dataset applied to the parental selection for producing inbred lines with satisfactory performance in primary and secondary traits simultaneously. The other one applied to demonstrate the application of producing inbred lines with high adaptability to different environments. Overall, the results showed that incorporating GEBV and genomic diversity into selection strategy based on the proposed selection index could assist in selecting superior parents to meet the desired breeding goals and increasing long term genetic gain. An R package, called as IPLGP, was generated to facilitate widespread application of the approach.